2020
DOI: 10.1021/acs.jpcc.0c04626
|View full text |Cite
|
Sign up to set email alerts
|

Germanium Possessing Facet-Specific Trap States and Carrier Lifetimes

Abstract: Previously, the notable differences in the band structure and changes in bond length and bond distortion between the semiconducting and metal-like planes of germanium have been used to understand the facet-dependent electrical conductivity properties of germanium wafers. To gain further insights into the appearance of electrical facet behaviors, impedance measurements were performed on the Ge{111}, {110}, and {100} wafers. Impedance data and several conductivity-related parameters were used to produce a diagra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 28 publications
(49 reference statements)
0
27
0
Order By: Relevance
“…7,16 To gain further insights, the most conductive Si and Ge {111} wafers were found to have the lowest surface trap state population and the shortest carrier lifetime, matching with their best electrical conductivity behavior. 17,18 GaAs wafers, however, do not show such surface trap state and carrier lifetime correlation to their conductivity properties. 19 In addition to surface-related electrical conductivity properties, Cu 2 O, Ag 2 O, Ag 3 PO 4 , SrTiO 3 , and other polyhedral crystals also present strong photocatalytic facet effects.…”
Section: ■ Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…7,16 To gain further insights, the most conductive Si and Ge {111} wafers were found to have the lowest surface trap state population and the shortest carrier lifetime, matching with their best electrical conductivity behavior. 17,18 GaAs wafers, however, do not show such surface trap state and carrier lifetime correlation to their conductivity properties. 19 In addition to surface-related electrical conductivity properties, Cu 2 O, Ag 2 O, Ag 3 PO 4 , SrTiO 3 , and other polyhedral crystals also present strong photocatalytic facet effects.…”
Section: ■ Introductionmentioning
confidence: 92%
“…To explain the emergence of the observed electrical facet effects, density functional theory (DFT) calculations have revealed the presence of an ultrathin surface layer (∼1 nm or less in thickness) with dissimilar band structures for various surface planes, which should lead to different degrees of surface band bending and facilitate or prevent charge transport across a particular crystal face. ,,, Furthermore, bond length and bond directions, as well as frontier orbital electron energy distribution, within the thin surface layer can show deviations or variations for the highly conductive crystal faces such as the Si (111) and Cu 2 O (111) planes, which should yield changes in the surface band structure. , These DFT results provide a more physical picture of the thin surface layer. Interestingly, the predicted structural deviations in the surface lattice planes may be observable, as seen in the high-resolution transmission electron microscopy (HR-TEM) images of SrTiO 3 crystals with slight atomic position deviations and noticeable peak shifts in the X-ray diffraction (XRD) patterns of polyhedral Cu 2 O crystals. , To gain further insights, the most conductive Si and Ge {111} wafers were found to have the lowest surface trap state population and the shortest carrier lifetime, matching with their best electrical conductivity behavior. , GaAs wafers, however, do not show such surface trap state and carrier lifetime correlation to their conductivity properties …”
Section: Introductionmentioning
confidence: 99%
“…In addition, the Schottky barrier heights were found to match with the electrical conductivity order of Ge wafers with the {111} surface having the lowest barrier . However, the Schottky barrier results do not agree with the conductivity properties of different Si wafers that the {111} surface has the largest barrier . The Schottky barrier is the energy difference between the conduction band edge of an n-type semiconductor (or valence band edge for a p-type semiconductor) and the metal work function .…”
Section: Introductionmentioning
confidence: 90%
“…18 The GaAs {111} surface is notably more conductive than the {100} surface, while the {110} surface is least conductive, especially at applied voltages below 5 V. 19 To provide more insights into the emergence of the electrical facet properties, impedance measurements have been performed to show the amount and energy distribution of trap states located within the band gap of Si and Ge. 20,21 In contrast to donor states generally with energies close to the conduction band, deep trap states have lower energies. 22 The impedance measurements also offer information on the charge carrier (electrons or holes) lifetimes.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Semiconductor crystals generally possess facet-dependent electrical conductivity properties, as revealed by conductivity measurements on single polyhedral Cu 2 O, Ag 2 O, TiO 2 , PbS, and Ag 3 PO 4 crystals. Moreover, intrinsic Si, Ge, and GaAs wafers also exhibit electrical facet effects. DFT calculations have revealed that the semiconductor facet effects should originate from the presence of an ultrathin surface layer with dissimilar band structures for different crystal faces. , DFT calculations further suggest that subtle variations in bond length, bond geometry, and frontier orbital electron energy distribution are present between metal-like and semiconducting surface planes of Si, Ge, and GaAs. Thus, slight variations at the bond and orbital levels contribute to changes in the band structure of the surface layer, which produces the observed facet-dependent electrical conductivity behaviors of semiconductors. More recently, electrochemical impedance measurements on Si, Ge, and GaAs wafers have revealed that the presence of deep trap states located within the band gaps is linked to their facet-dependent electrical conductivity properties. The idea of the ultrathin surface layer with facet-specific band structures can also explain the observations of facet effects in the photocatalytic activities and optical properties of semiconductor crystals. Although several examples of semiconductors possessing strongly facet-dependent conductivity properties have been demonstrated, some unexpected phenomena can still emerge in other materials, as seen in the diverse interfacial plane-related photocatalytic outcomes of semiconductor heterostructures . Previously, size-tunable strontium titanate (SrTiO 3 ) cubes and {100} face-truncated rhombic dodecahedra with a perovskite crystal structure have been synthesized .…”
Section: Introductionmentioning
confidence: 99%